A history of crime in Australia - Cushing, Nancy, author.
1 online resource
Keywords: "This book provides a lively and accessible account of Australia's most prominent crimes and criminals of the nineteenth and twentieth century, and offers an informative background for those seeking to understand crimes committed today. This book examines the imposition of English law on this ancient continent, and how its operation affected both transported offenders from Great Britain and Ireland, and the Aboriginal and Torres Strait Islander peoples whose own systems of laws were overlaid. Drawing upon cutting-edge research in the field, original work by the author, and essays from leading crime history researchers, it addresses the question of whether there was an "Australian Underworld". In doing so, it provides background for well known offenders including bushranger Ned Kelly and the razor gangs of the 1920s and for sensational crimes like the Mount Rennie Outrage, the Pyjama Girl Mystery and the Shark Arm Murder and the miscarriage of justice following the disappearance of Azaria Chamberlain at Uluru in 1980. Through these case studies, the book draws out points of tension and cohesion within Australian society, exposing the enduring anxiety around those who were considered to be outsiders, and how the criminal justice system was used to manage these concerns. This book includes a guide to conducting research in the field of Australian crime history and sources for further study. Designed as an introductory text for students, this book will be of interest to those studying criminology and crime history, and anyone who would like to deepen their understanding of crime's place in Australia's social and cultural history"--